A tribo-dynamic based pitting evolution model of planetary gear sets: A topographical updating approach. (15th April 2022) - Huangfu, Yifan; Dong, Xingjian; Chen, Kangkang; Tu, Guowei; Long, Xinhua; Peng, Zhike
Highlights: A fast dynamic load distribution algorithm is proposed to obtain the dynamic load. The iterative topography updating is involved in the dynamic pitting evolution . The pitting prediction model is verified by experimental results. The probability distribution of pitting is investigated from a physics-based perspective . The tribo-dynamic behaviors of pitted gears during the life-cycle evolution are evaluated. Abstract: Considering the coupling effects of the tribology and dynamics, a dynamic pitting evolution model of planetary gear sets is developed. A fast dynamic load distribution algorithm is proposed to obtain the dynamic contact load considering complex pitting topography. Then the mixed elastohydrodynamic lubrication theory is adopted to acquire the tribological parameters. Combing the dynamic load and Zaretsky's fatigue criterion, a contact fatigue model is developed to predict the pitting topography during the degradation process. An iterative algorithm framework is developed to realize the topographical updating in the dynamic pitting prediction. The effectiveness of the proposed model is demonstrated using two experimental examples. The probability distribution of the pitting location is investigated using the proposed model. It is revealed that the gamma distribution is more consistent with the pitting distribution along the involute direction than the normal distribution. Owing to the "competition mechanism" of the pitting and surface wear, the pitting center approaches the pitch point with the increase of the surface roughness. The proposed model is capable of evaluating tribo-dynamic behaviors of planetary gear sets during the life-cycle degradation process of pitting failure. Moreover, it can provide theoretical guidance for the pitting fault mechanism and model-based fault diagnosis. Graphical abstract: Image, graphical abstract